Packaging Methods and Storage Duration on the Organoleptic, Microbiological, and Chemical Qualityof Patin fish-Tempeh Nugget - Hesti Atasasih; Irma Susan Paramita; Dewi Rahayu; Nurlisis Nurlisis; Ana Yuliah Rahmawati (Jurnal Ilmiah Kesehatan (JIKA), 2026)
The modification of nuggets by incorporating tempeh can improve their nutritional value. NUPATE (Patin Fish–Tempeh Nugget) is a product made from catfish and tempeh with the best formulation consisting of 30% catfish and 70% tempeh. This study aimed to determine the effect of packaging methods and storage duration on the organoleptic, microbiological, and chemical quality of NUPATE. An experimental study was conducted using a factorial Completely Randomized Design (CRD) with packaging methods (vacuum and non-vacuum), storage duration (0, 10, 20, and 30 days), and storage temperatures (20–25°C, >2–10°C, -4–2°C, and -18 to -23°C) as factors. Organoleptic evaluation was carried out by 30 untrained panelists. The results showed that packaging methods and storage duration at different temperatures significantly affected NUPATE quality (p < 0.05). Total Plate Count (TPC) analysis indicated a significant difference between vacuum and non-vacuum packaging (p < 0.05), while protein and fat content decreased with increasing storage duration (p < 0.05). Vacuum packaging at freezer temperature (-18 to -23°C) was the most effective method for maintaining NUPATE quality for up to 30 days.